Eptolagraph Palma - Díaz Ortiz, Pedro (2019)
Ricardo Palma has cultivated many literary genres. Journalism, epistolary, and literary translation are the least known of them. In general, this paper is about the letters sent by Ricardo Palma to Peruvian, Hispanic-American and Spanish writers, and, likewise, with the letters sent by Peruvian, Hispanic American and Spanish writers to Ricardo Palma.